Novel HLA‐C*07:314 allele identified by sequence‐based typing in a French lymphoblastic leukemia patient. Issue 6 (16th October 2013) - Elsermans, V.; Top, I.; Kuzio, E.‐M.; Ballieu, S.; Labalette, M.
<x xml:space="preserve">Abstract</x> A novel human leukocyte antigen‐C (HLA‐C) allele, C*07:314, was identified in a French acute lymphoblastic leukemia patient.